Peningkatan Hasil Belajar Siswa pada Pembelajaran IPA menggunakan Model CTL di Kelas V Sekolah Dasar - Aulia, Akrima; Zuryanty, Zuryanty; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study is to describe improvement of student learning outcomes in science learning using the Contextual Teaching and Learning model. This research is a classroom action research (CAR), using short qualitative and quantitative methods. This study consists of two cycles with observation sheet research instruments test sheet. The research subjects were teachers and fifth grade students of elementary school 01 Kapau, Agam Regency, amounting to 25 people.The results showed an increase in: (a) Plans in the first cycle were on average 8 5.75 % (B ) cycle II to 96 % (SB), (b) Implementation of cycle I aspect of the teacher averaged 79 % (B) cycle II to 94.4 % (SB) and cycle implementation The aspect of students with a score of 75 % (C) cycle II to 91, 7 % (SB) , (c) student learning outcomes in cycle I on average were 71.73 ( C ) cycle II to 83 (B). Concluded that CTL models can improve science learning outcomes for fifth grade students of elementary school 01 Kapau, Agam Regency.Keywords: contextual teaching and learning (ctl) model, sains